Pengaruh Beban Kerja dan Sistem Informasi Manajemen Terhadap Kinerja Pegawai Perusahaan Daerah Air Minum (PDAM) Kota Probolinggo - Wahyu Dwil Laksono; R. Abdul Haris; Mutinda Teguh Widayanto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to determine whether the Workload and Management Information Systems have a simultaneous and partial effect on the Performance of Employees at the Regional Drinking Water Company (PDAM) of Probolinggo City. The research employed a descriptive quantitative approach, with Workload and Management Information Systems as variables affecting Employee Performance. The sample size for this study was 51 respondents, all of whom were employees of PDAM Probolinggo. Sampling was done using a saturation sampling technique, where all employees were included in the sample. To prove and analyze this, validity and reliability tests, classical assumption tests, R² determination analysis, multiple linear regression tests, and F (simultaneous) and t (partial) tests were used. The results showed that: 1) Simultaneously, Workload and Management Information Systems have an effect on Employee Performance at PDAM Probolinggo City. This is based on the F-value being greater than the F-table value (25.021 > 1.43). Thus, the hypothesis testing on the F-test (simultaneous) indicates that there is a combined effect of Workload and Management Information Systems on Employee Performance. 2) Partially, both factors influence Employee Performance at PDAM Probolinggo City. The partial test results show that Workload (X1) has a regression coefficient of -3.390 < -2.010, so H0 is rejected and Ha is accepted, while Management Information Systems (X2) has a regression coefficient of 6.017 > 2.010, so H0 is rejected and Ha is accepted. Both variables have a significance value < 0.001. Thus, the t-test (partial) results show a significant negative effect of Workload and a significant positive effect of Management Information Systems on Employee Performance at PDAM Probolinggo.